Computer animation magic - Valois, Geoffrey de; Michelson, Steve; Cohen, Donna; One Pass Productions; Cohen Computer Graphics (Oak Forest, IL: MPI Home Video ; Digital Vision Home Video, 1988)
The use of computers and computer graphics programs has assisted in the production of animation and image processing in ways that have truly revolutionized these and allied fields
Designed by Donna Cohen ; executive producer, Steve Michelson ; edited by Kitty Rea [&] Geoffrey de Valois
Narrated by Bruce Robertson
Keywords: Computer animation; Computer drawing